Urgensi spiritual well-being (SWB) pada kelompok lansia: systematic literature review (SLR) - Zuhri, Ahmad Minan; Mulawarman, Mulawarman; Mulyani, Petra Kristi (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2025)
The increasing number of elderly groups poses challenges such as loneliness, decreased physical abilities, and mental health problems. Spiritual well-being is considered a key factor in helping the elderly overcome these problems. Through Spiritual Well-Being can significantly overcome these aspects in the lives of the elderly. This study aims to analyze the importance of Spiritual Well-Being (SWB) in the lives of the elderly to provide direction and guidance in living life. This study uses the Systematic Literature Review (SLR) method with the PRISMA diagram. The results of the study showed that (1) the impact of SWB on the elderly group is an increase in well-being, quality of life, mental and physical health, and reducing stress and depression levels. (2) factors that influence SWB in the elderly group are social support, social participation, self-perception, religious beliefs, education and economic levels and culture and traditions.